Acoustic surveillance of cough for detecting respiratory disease using artificial intelligence. Issue 2 (30th May 2022) - Gabaldón-Figueira, Juan C.; Keen, Eric; Giménez, Gerard; Orrillo, Virginia; Blavia, Isabel; Doré, Dominique Hélène; Armendáriz, Nuria; Chaccour, Juliane; Fernandez-Montero, Alejandro; Bartolomé, Javier; Umashankar, Nita; Small, Peter; et al.
Research question: Can smartphones be used to detect individual and population-level changes in cough frequency that correlate with the incidence of coronavirus disease 2019 (COVID-19) and other respiratory infections? Methods: This was a prospective cohort study carried out in Pamplona (Spain) between 2020 and 2021 using artificial intelligence cough detection software. Changes in cough frequency around the time of medical consultation were evaluated using a randomisation routine; significance was tested by comparing the distribution of cough frequencies to that obtained from a model of no difference. The correlation between changes of cough frequency and COVID-19 incidence was studied using an autoregressive moving average analysis, and its strength determined by calculating its autocorrelation function (ACF). Predictors for the regular use of the system were studied using a linear regression. Overall user experience was evaluated using a satisfaction questionnaire and through focused group discussions. Results: We followed-up 616 participants and collected >62 000 coughs. Coughs per hour surged around the time cohort subjects sought medical care (difference +0.77 coughs·h −1 ; p=0.00001). There was a weak temporal correlation between aggregated coughs and the incidence of COVID-19 in the local population (ACF 0.43). Technical issues affected uptake and regular use of the system. Interpretation: Artificial intelligence systems can detect changes in cough frequency that temporarily correlate with the onset of clinical disease at the individual level. A clearer correlation with population-level COVID-19 incidence, or other respiratory conditions, could be achieved with better penetration and compliance with cough monitoring. Artificial intelligence software installed in smartphones can detect changes in cough frequency associated with medical consultations. With adequate uptake and use, these tools could help detect the onset of respiratory disease in a population. https://bit.ly/3qSuaIV